All Days 2013
DOI: 10.2118/164900-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of Viscoelastic Surfactant Fluids Using Nanoparticles

Abstract: Viscoelastic surfactant (VES) based fluids are used in many applications in the oil industry. Their viscoelastic behavior is due to the overlap and entanglement of long wormlike micelles. The growth of these wormlike micelles depends on the charge of the head group, salt concentration, temperature, and the presence of other interacting components. The problem with these surfactants is that they are expensive and used at temperatures less than 200°F.The viscoelasticity of nanoparticle-networked VES fluid system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…15 Their viscoelastic behavior is due to the overlap and entanglement of long wormlike micelles. 16 In straight tubing experiments, fluid concentration and pipe shear are both having notable effects on fluid elasticity. 17 VES has been developed to take place of polymer solution in a board range of reservoir conditions with good injectivity even when using very viscous VES solutions (i.e., up to 1000 mPa s) and low permeability reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Their viscoelastic behavior is due to the overlap and entanglement of long wormlike micelles. 16 In straight tubing experiments, fluid concentration and pipe shear are both having notable effects on fluid elasticity. 17 VES has been developed to take place of polymer solution in a board range of reservoir conditions with good injectivity even when using very viscous VES solutions (i.e., up to 1000 mPa s) and low permeability reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…20 Studies illustrated that the addition of nanoparticles-MgO or ZnO improved the thermal stability of VES micellar structures in CaBr 2 and CaCl 2 brines up to 275 °F (135 °C) and showed an improved viscosity yield at different shear rates. 16 Series of VES fluids have been developed that the temperature range has been extended to 300 °F21 and have good stability in 18.6% highly saline brine. 22 Additionally, fluid-loss controlling technology improves the performance of VES.…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement of VES-based fluids was accomplished with the development of a system that is thermally stable up to 275°F (Gurluk et al 2013). Base fluids were prepared with either 2 or 4 vol% amidoamine oxide surfactant in 14.2 ppg CaBr 2 brine.…”
Section: A2 Pseudo Crosslinkersmentioning
confidence: 99%
“…The oscillatory rheological measurements for nanoparticles in viscoelastic surfactant fluids noted that the nanoparticles apparently strengthened the micelle-micelle interactions. Lab proppant settling tests demonstrated that the nanoparticle induced VES micelle network structures that dramatically increased the capacity of the surfactant fluid to suspend and transport proppant in well treatments Huang and Crews, 2007;Crews and Huang, 2008;Crews and Ahmed, 2012;Gurluk, et al, 2013). M.F.…”
Section: Introductionmentioning
confidence: 99%